n Marxisties-feministiese ondersoek van Wilma Stockenström se roman, Die kremetartekspedisie - Gardner, Judy Hilary (Rhodes University, Faculty of Humanities, School of Languages, 1989)
Chapter is an exploration of the meanings which may underly the title of this novel. I have tried initially to establish what kind of "expedition" is undertaken, and have come to the conclusion that "expedition" has a multidimensional meaning, that it implies a search, an expedition into different things: an expedition to the city of rose-quartz; the slave woman's expeditions from the baobab tree and back; an inner expedition to gain self-knowledge; an expedition into womanhood; an expedition into the history of Africa, into religion, into language. The second part of the chapter examines the nature of "baobab", since this tree, like the "Tree of Life", is regarded as one growing upside-down. It is this upside-down nature of the tree which led me to believe that many existing stereotypes and myths are turned upside-down in the novel: about slaves, about woman, language, the Afrikaans literary tradition, the "traditional" structure of the novel, culture transcending nature, the slave woman's language. In chapter 2 I have examined only one of these expeditions, viz. the slave woman's inner expeditions consisting of her experiences as a slave and her journeys of reminiscence. These journeys at the same time embrace all the other expeditions. Her inner expeditions are signified by a number of codes, which fulfil literally the function of processes of knowledge, of self- knowledge, as well as of systems in which meaning is contained. By undertaking this inner expedition, the woman gains greater clarity of vision concerning her own existence and the existence of man/woman in general. Chapter 3 deals mainly with the concept of possession/ownership, which results in two diametrically opposed groups: the owner class and the owned class. The peculiar institution of slavery has given rise to these two irreconcilable groups, and therefore a brief history of slavery is included in this chapter. The slave woman is initially one of the owned class, but through indoctrination, she too aspires to become a member of the owner class. In the second half of the chapter, then, the woman is discussed as owner. Her position becomes a reflection of the position of her owners, to illustrate the peculiarity of the capitalist system in which there will always be the rulers and the subjects, the oppressor and the oppressed, the owner and the owned.
Keywords: Stockenström, Wilma -- Criticism and interpretation; Stockenström, Wilma. Kremetartekspedisie